Impact of immersing university and high school students in educational linear narratives using virtual reality technology. (December 2020) - Calvert, James; Abadia, Rhodora
Abstract: Immersive Virtual Reality (VR) is in its early days of educational adoption. This research aims to explain the benefits of VR in transforming learning and student experiences in classrooms. The experiment involved students using an educational VR experience that features an immersive narrative that puts students in the centre of a historical moment in World War Two. Two separate studies were conducted. One with high school students in Australia who would normally be studying the topic. And the other, University students in India, with no prior knowledge or awareness of the topic. Student participants used one of two different versions of Kokoda VR; six-degrees of freedom virtual reality or 360° video. Both the university and high school students using the virtual reality condition reported higher engagement, presence, empathy and better knowledge mastery than the 360° video groups. These features were also slightly higher in the university student group than in the high school student group except for the knowledge mastery where the high school students performed better. These findings indicate there is potential for immersive narrative VR experiences to provide students with new experiences and provide both cognitive and affective benefits. Highlights: Immersive VR can increase cognitive and affective outcomes in student learning. Higher affective scores for university students when using immersive VR. Higher test scores for high school students due to deeper perception experience. Higher affective and cognitive scores for immersive VR compared to 360° video.